High efficacy and enhanced synergistic activity of the novel siderophore-cephalosporin cefiderocol against multidrug-resistant and extensively drug-resistant Klebsiella pneumoniae from inpatients attending a single hospital in the United Arab Emirates - Lana Daoud; Farah Al-Marzooq; Akela Ghazawi; Febin Anes; Timothy Collyns (Elsevier, 2023)
Background: Cefiderocol (CFDC) is a novel siderophore-cephalosporin, which usually penetrates the bacteria through the iron-uptake pathways. Data is limited on the factors affecting CFDC activity and methods for overcoming resistance development. Synergistic approaches are needed to tackle antimicrobial resistance. This study aimed to determine CFDC activity on Klebsiella pneumoniae isolates from patients attending a single hospital in the United Arab Emirates (UAE), to explore the effect of β-lactamases on CFDC activity and to enhance CFDC susceptibility in both iron-depleted and iron-enriched conditions. Methods: We investigated 238 K. pneumoniae strains from diverse clinical sources. β-lactamase genes were detected by PCR. Susceptibility to CFDC and 12 comparator antibiotics were tested. Combinations of CFDC with β-lactamase inhibitors (BLIs) and/or an outer membrane (OM) permeabilizer (polymyxin B nonapeptide) were tested in iron-depleted and iron-enriched conditions. Results: CFDC exhibited efficacy of 97.9%, against multidrug-resistant (MDR), and extensively drug-resistant (XDR) strains, in addition to strains resistant to the last resort drugs such as colistin and tigecycline, including dual carbapenemase-producers (blaNDM and blaOXA-48-like) with MIC ≤ 0.06-8 µg/ml. It was effective in killing strains with single and multiple β-lactamases; however, it lost activity in iron-enriched conditions. Synergy was achieved with dual combination of CFDC and BLIs, especially avibactam, which caused a significant reduction in MICs even in iron-enriched conditions. A significant reduction was seen with the triple combination including an OM permeabilizer plus avibactam. Killing-kinetic studies proved that the combination therapy caused dose reduction and faster killing by CFDC than the monotherapy. Conclusions: CFDC was deemed effective against MDR and XDR K. pneumoniae. Synergistic combination of CFDC with BLIs and OM permeabilizers could be effective to treat infections in iron-rich sites, but this should be investigated in vivo.